METHAPOR IN “A WALK TO REMEMBER” NOVEL BY NICHOLAS SPARKS - Maisarah , Iskandar Zulkarnain, Yunita Mutiara Harahap (EXCELLENCE: Journal of English and English Education, 2021)
This research was focused only to find metaphor in “A Walk To Remember” novel. The research was conducted by using descriptive qualitative method. The data were collected from chapter 1 until chapter 6 of the novel. The finding of the research showed that there were 50 lines of metaphor which were classified into three types of metaphor, namely structural metaphor (36), orientational metaphor (9), and ontological metaphor (5). The most dominant type of metaphor used in the novel was structural metaphor (36). It means that the point of the novel was a description of imaginary art work of the author as if the events in the novel were literally true and really happening. In addition, the novel itself was a metaphor that providing structure and analogy to real world.